"I am the Lord your Healer". A Philological Study of the Root Rapa’ in the Hebrew Bible and in the Ancient Near East - Brown, Michael L. (1985)
Ph.D. diss.; Adviser: B. A. Levine; Order No. DA8604041; Cf. DissAbstr 46/12 (June 1986) 3701-A.